2009
DOI: 10.1111/j.1365-2672.2009.04144.x
|View full text |Cite
|
Sign up to set email alerts
|

Fate ofSalmonellain dry confectionery raw materials

Abstract: Aims:  To study the behaviour of salmonellae inoculated in the dry, raw materials, related to chocolate confectionery manufacture, as affected by the strain, cell preparation method and storage temperature. Methods and Results:  Outbreak and non outbreak‐associated salmonellae were used for the inoculation of cocoa butter oil, crushed cocoa and hazelnut shells, cocoa beans and almond kernels. Dry matrices were inoculated with lawn‐collected and broth‐grown cells and were stored at 5 and 21°C for 21 days. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 35 publications
1
35
0
2
Order By: Relevance
“…Komitopoulou and Penaloza (2009) found that inoculated Salmonella could survive for 3e4 weeks on dry, raw materials including crushed cocoa and hazelnut shells, cocoa beans, and almond kernels at both room temperature and 5 C. Salmonella is typically inhibited by a w < 0.91, but the a w of these substances were likely much lower. It can be concluded that any heat treatment of food must be sufficiently high to destroy Salmonella while still providing a quality product.…”
Section: Cross Contamination and Pathogen Survivalmentioning
confidence: 98%
“…Komitopoulou and Penaloza (2009) found that inoculated Salmonella could survive for 3e4 weeks on dry, raw materials including crushed cocoa and hazelnut shells, cocoa beans, and almond kernels at both room temperature and 5 C. Salmonella is typically inhibited by a w < 0.91, but the a w of these substances were likely much lower. It can be concluded that any heat treatment of food must be sufficiently high to destroy Salmonella while still providing a quality product.…”
Section: Cross Contamination and Pathogen Survivalmentioning
confidence: 98%
“…Salmonella can survive from several weeks to several years on dry surfaces (21,36,48), eggshells (55), almond kernels (68), pecans (11), and dry confectionery raw materials (47). During the last decade, Salmonella has been involved in several national and international outbreaks related to consumption of low-water-activity foods such as snacks, almonds, peanut butter, chocolate, and paprika (4,5,6,37,45,71).…”
mentioning
confidence: 99%
“…Salmonella is widespread in nature and survives in dry foods for weeks, months, or even years (Chang et al 2013 ;Beuchat and Mann 2010a ;Komitopoulou and Peñaloza 2009 ;Beuchat and Scouten 2002 ;Burnett et al 2000 ;Archer et al 1998 ). Food composition, water activity, and temperature collectively infl uence its survival in foods (He et al 2011 ;Mattick et al 2001 ;Corry 1974 ;Dega et al 1972 ;Moats et al 1971 ).…”
Section: Pathogens Of Concern In Low-water Activity Foods and Spicesmentioning
confidence: 94%